The species of Ecnomocephala Gibson (Hymenoptera: Eupelmidae) - Gibson, Gary A. P. (Zootaxa, 2019)
The species of the New World genus Ecnomocephala Gibson (Hymenoptera: Chalcidoidea: Eupelmidae: Eupelminae) are revised. Seven species are recognized, the type species, E. townesi Gibson, 1995 (♀♂: USA), and the following six new species: E. ashei Gibson n. sp. (♀♂: French Guiana, Guyana, Venezuela), E. boliviensis Gibson n. sp. (♀: Bolivia), E. gilli Gibson n. sp. (♀♂: Brazil, Costa Rica, Panama), E. hypha Gibson n. sp. (♀: Costa Rica), E. retia Gibson n. sp. (♀: Mexico), and E. speculum Gibson n. sp. (♀: Colombia, Ecuador, Peru). The species are illustrated through macrophotography and keyed. Morphology of the sexes is compared to each other relative to sexual dimorphism and examined for implications for inferring function, character-state evolution, and phylogenetic relationships within the subfamily.